FAKTOR-FAKTOR PENDUKUNG MINAT BERWIRAUSAHA SISWA SMK PANCASILA 5 WONOGIRI - DARMAWATI , INDAH (2011)
Vocational School as a sub-national education system has a big enough opportunity to participate in the development of economic system which is supported by business people who are creative, innovative and has a resistance to change. How this can be done by encouraging students to utilize existing knowledge and skills to develop business, in order to work independent of entrepreneurship. The role of parents is also very important for growing interest in entrepreneurship for students. Parents are the foundation stone for children's personal future. Given that entrepreneurship education for lifetime. So the period of education by parents to their children do not age restricted. Therefore, the researcher took the formulation of the problem: 1. Are there any influence of parental support, facilities, and excellent service to the students' interest in entrepreneurship SMK Pancasila 5 Wonogiri simultaneously? 2. Are there any influence of parental support towards students' interest in entrepreneurship SMK Pancasila 5 Wonogiri? 3. Are there infrastructure influence on students' interest in entrepreneurship SMK Pancasila 5 Wonogiri? 4. Are there any influence on the interest-rate service entrepreneurship SMK Pancasila 5 Wonogiri? The purpose of this study to analyze the influence of parental support towards students' interest in entrepreneurship SMK Pancasila 5 Wonogiri; To analyze the effect of infrastructure on student interest in entrepreneurship SMK Pancasila 5 Wonogiri; To analyze the effect of interest-rate service entrepreneurship SMK Pancasila 5 Wonogiri; To analyze the influence parental support, facilities and excellent service to the students' interest in entrepreneurship SMK Pancasila 5 Wonogiri simultaneously. This research is a quantitative and type of correlation which aims to discover the relationship between two variables. Methods of data collection in the form of questionnaires, documentation and observation. From a population of 232 students, so that as the sample totaled 139 students or 1,669%. The results of correlation factors supporting student interest in entrepreneurship, selected significance level which means 0.003 <0.05. Withdrawal of conclusion: reject Ho, thank Ha. So we can conclude that there is a correlation between the factors supporting the interest in entrepreneurship students at SMK Pancasila 5 Wonogiri.